Respostas

2013-10-29T18:35:18-02:00
  • Usuário do Brainly
2013-10-29T21:23:09-02:00
A - 3b = 4 .(-2)
2a - 4b = 9
------------
-2a + 6b = - 8
2a - 4b = 9
--------------
2b = 1
b = 1/2
------------
sendo:
a - 3b = 4
a - 3*1/2 = 4
a - 3/2 = 4
mmc da 2
2a/2 - 3/2 = 8/2
elimine os denominadores (2)
2a - 3 = 8
2a = 8 + 3
2a = 11
a = 11/2
-----------
logo:

a = 1/2
b = 11/2
------------
substitua os valores para tirar a conclusão verdade:

2a - 4b = 9
2*(11/2) - 4*(1/2) = 9
22/2 - 4/2 = 9
11 - 2 = 9 -------portanto verdadeiro.

ESPERO TER AJUDADO!